Variação nictemeral e lunar na ictiofauna em poças de maré em um recife de arenito no litoral Oeste do Ceará - Mendonça, Thiago Silva (2017)
The nictimeral variation has strong influence on the relative abundance of several species, altering the composition and richness of fish assemblages. The lunar variation is another natural cycle that can also influence this relative abundance. The objective of this research was to describe the lunar and nictemeral variation of the ichthyofauna of the tidal pools of Pedra Rachada beach, Paracuru, west coast of Ceará. In August and September of 2016, three pools with different areas and depths were sampled, with visual census. Twelve censuses were carried out in each pool, distributed equally between the daytime and nighttime periods (nocturnal censuses were also divided between full and new moon phases, with three censuses in each pool in each lunar phase). During the day 1.732 individuals belonging to 24 species and 17 families were recorded, being Haemulidae and Labridae the most representative in number of species (4). In the night, 436 individuals were recorded from 16 species and 12 families, with Haemulidae being the most representative (5). The species H. plumieri, H. parra and A. chirurgus presented high values of density in both periods of the day. The nMDS showed a clear segregation between day and night, but did not indicate lunar influence on the ichthyofauna. A PERMANOVA confirmed the results of the nMDS for the periods (p = 0.0001) and for moon phases (p = 0.6645). The trophic category most representative in number of species and density of individuals were mobile invertebrate feeders in both periods. Only one class of length A (up to 5 cm) showed a significant difference in density between day and night. The values of diversity and evenness were high, but the Pielou index presented a significant difference between the periods. Both indices did not show significant difference with the lunar variation. It is important to note the importance of further studies with longer observation time, for example, an influence of seasonal events such as rainy and windy periods on the ichthyofauna during the day and at night, as well as assessing the influence of other phases of the moon on Structuring of assemblies. This increases knowledge about the ichthyofauna present on the reefs of the regions of the semi-arid region of the Northeast.